(untitled) (Annals of the University of Bucharest. Political Science Series, 2025)
Who has led Poland in the past 20 years, technocrats or politruks? Were those placed at the top of ministries merely party cadres, or were they experts in the domain of their ministerial activity? To uncover the answer, the present paper surveys 257 ministers spread across 10 governments and 19 years, starting with the 2001 government led by Leszek Miller and ending with the second Mateusz Morawiecki cabinet instated in November 2019. The findings suggest that the share of technocratic ministers – defined minimally as individuals who received formal education in the field of their ministerial activity – varied from 65% in 2001 to 35% in 2006, averaging at 50.19% in the entire period. 129 ministers have been technocrats and 128 politruks, as defined in this paper. The latter, however, have steadily increased their share since 2000. Consequently, half of the Polish ministers were politruks – creations of the political parties, non-experts that headed National Defense, Health, Interior, and other Ministries of paramount importance.